An Analysis of the Interpretation of Verses About Religious Pluralism in the Book of Tafsir Lubab at-Ta'wil fi Ma'ani at-Tanzil, Tafsir An-Nasafi, Tafsir Ruh Al-Ma'ani and Tibyan fi Tafsir Al-Qur'an (Study of Tafsir Muqaran ) - Amalia, Ilma; Fitriana Lubis, Mumun; Komarudin, Edi (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2024)
Differences are inevitable, taking any form imaginable, from who gets to define right and wrong to who makes it to the afterlife. This is a question that sparks crucial discussions among religionists. Tafsir scholars certainly have their own interpretations of verses relating to the afterlife and views of salvation. Religious pluralism is something that is difficult to avoid, because it is impossible to gather various beliefs under one religious banner. However, can this plurality in religion be recognized by all religions or is it only a group of people who claim justification for themselves and their group who will truly gain salvation? Departing from this background, the author presents several discussions that will be discussed in this article, namely: the meaning of religious pluralism, verses from the Qur'an about religious pluralism, biographies of commentators, interpretation of pluralism verses according to tafsir books, as well as comparative writers of tafsir and the interpretation of the pluralism verses that they wrote in their tafsir. The purpose of this article is to reveal a comparison of the interpretation of pluralism verses and to compare the biographies of the authors in terms of their interpretation methodology. The method used by the author in this article is a qualitative method with a narrative study approach which focuses on the biography or background of each interpreter and their views on pluralism verses which are being widely studied at this time.